AAVP displaying octreotide for ligand-directed therapeutic transgene delivery in neuroendocrine tumors of the pancreas - Smith, Tracey L. (Proc Natl Acad Sci U S A, 2016)
Patients with inoperable or unresectable pancreatic neuroendocrine tumors (NETs) have limited treatment options. These rare human tumors often express somatostatin receptors (SSTRs) and thus are clinically responsive to certain relatively stable somatostatin analogs, such as octreotide. Unfortunately, however, this tumor response is generally short-lived. Here we designed a hybrid adeno-associated virus and phage (AAVP) vector displaying biologically active octreotide on the viral surface for ligand-directed delivery, cell internalization, and transduction of an apoptosis-promoting tumor necrosis factor (TNF) transgene specifically to NETs. These functional attributes of AAVP-TNF particles displaying the octreotide peptide motif (termed Oct-AAVP-TNF) were confirmed in vitro, in SSTR type 2-expressing NET cells, and in vivo using cohorts of pancreatic NET-bearing Men1 tumor-suppressor gene KO mice, a transgenic model of functioning (i.e., insulin-secreting) tumors that genetically and clinically recapitulates the human disease. Finally, preclinical imaging and therapeutic experiments with pancreatic NET-bearing mice demonstrated that Oct-AAVP-TNF lowered tumor metabolism and insulin secretion, reduced tumor size, and improved mouse survival. Taken together, these proof-of-concept results establish Oct-AAVP-TNF as a strong therapeutic candidate for patients with NETs of the pancreas. More broadly, the demonstration that a known, short, biologically active motif can direct tumor targeting and receptor-mediated internalization of AAVP particles may streamline the potential utility of myriad other short peptide motifs and provide a blueprint for therapeutic applications in a variety of cancers and perhaps many nonmalignant diseases as well.